HUBUNGAN ANTARA MOTIVASI DENGAN HASIL BELAJAR MATA PELAJARAN IPA TERPADU SISWA KELAS VIII UPTD SMPN 1 KUPANG TENGAH - Maria Santanis Filomena Banola; Moses K. Tokan; Mario J. Santrum (SINERGI : Jurnal Riset Ilmiah, 2026)
Education is the primary means of improving the quality of human resources, thus the success of the learning process is an important indicator of educational quality. One of the internal factors that plays a major role in determining student learning success is learning motivation. This study aims to determine the relationship between learning motivation and learning outcomes in Integrated Science subjects for grade VIII students at the UPTD of SMPN 1 Kupang Tengah. This study uses a quantitative approach with a correlational research type. The study was conducted in March of the 2024/2025 academic year with a sample of 60 students from grades VIII C and VIII D. The research instruments were a learning motivation questionnaire and a document of Integrated Science learning outcomes. Data collection techniques were carried out through questionnaires, observations, interviews, and documentation studies. Data analysis used the Pearson Product Moment correlation test with the help of the IBM SPSS Statistics 22 program, and was supported by validity, reliability, normality, homogeneity, and hypothesis testing. The results of the correlation analysis obtained a value of r = 0.594 with R Square = 37.21% which means that learning motivation contributes 37.21% to student learning outcomes. The hypothesis test shows a calculated F value = 90.850 with a significance of 0.000 < 0.05, so it can be concluded that there is a positive and significant relationship between learning motivation and learning outcomes. Thus, the higher the student's learning motivation, the better the Integrated Science learning outcomes achieved